Optimalisasi Kinerja Staff melalui Pengelolaan Beban Kerja dan Stres Kerja di PT YCH Indonesia - Ihsan Mustaqim; Asti Nur Aryanti; Ridlwan Muttaqin (Universitas Persada Indonesia YAI, 2026)
This research was designed to examine how workload and job stress reduction can improve staff performance at PT YCH Indonesia. This research used a quantitative method and followed an exploratory research approach. This study involved 329 staff members, and the sampling method used simple random sampling, resulting in a sample of 181 respondents. The research results explain that workload has a significant impact on staff performance, with a t-value of 4.885 and a significance 0.000. Job stress has an impact on staff performance, with a t-value of 7.962 and a significance level of 0.000. At the same time, workload and job stress significantly influence staff performance, with an F-value of 88.951 and a significance f 0.000. Changes in staff performance at PT YCH Indonesia were largely due to differences in workload and job stress, which reached 49.4%. The other 50.6% of changes were caused by many elements not included in the study.